THE DISPUTES OF RATÉB SIRIBÈE IN ACEH - Muchsin, Misri A; Hadi, Abdul; Manan, Abdul; Putra, Rahmad Syah (State Islamic University North Sumatra, 2021)
Abstract: This study discusses the foundation of Sufi tenet developed by Shaykh Amran Waly and the communities’ response to the integration of the tenet – the Study Council of Sufism Tawhîd (MPTT) and ratéb siribèe (one-thousand dzikr)–within the northern and eastern Aceh, Indonesia. Qualitative approach was implemented as the observation, in-depth interviews and documentation studies were due to collect the data. MPTT and ratéb siribèe as its integration aim to restore the grandeur of Acehnese people in the past. However, the tenet was responded in many ways by the communities. Some considered that MPTT and ratéb siribèe could act as a means of practicing Sufism, while the others assumed that the teachings developed were deviant since those contain the style of Ibn al-‘Arabî and al-Jîlî Sufism– once considered heretical with the concept of wahdah al-wujûd (unity of existence), which is dissimilar with the Sufism concept–wahdah al-syuhûd (unity of appearance). Keywords: Amran Waly, MPTT, ratéb siribèe, sufism, tawhîd